I am reading a mathematics book for poker and came across this equation:

$P$ = pot bets
$c$ = frequency player x calls
bluff bet = 1

(pot size)(frequency x folds) = (bluff bet)(frequency x calls)
$P(1-c) = c$
$c = P/(P+1)$

I need help to understand the steps between.


1 Answer 1



$P -Pc=c$

$P = c+Pc$

$P= c(P+1)$

$c = P/(P+1)$

Is this what you mean?

  • $\begingroup$ Yes, thank you! But I still have a problem understanding $c + Pc$ to $c(P+1)$. I'm so new to this. :D $\endgroup$
    – JimmyRare
    Jul 13, 2014 at 12:28
  • $\begingroup$ It's factorization. Try multiplying out c(P+1) and see that you get the same. $\endgroup$
    – user119615
    Jul 13, 2014 at 12:31
  • $\begingroup$ Indeed. I guess I'll head back to algebra fundamentals. $\endgroup$
    – JimmyRare
    Jul 13, 2014 at 12:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.